The 37‐kDa laminin receptor precursor regulates the malignancy of human glioma cells. (October 2016) - Wu, Hongjie; Li, Jing; Xu, Dongxiao; Jv, Donghui; Meng, Xiaofeng; Qiao, Peng; Cui, Tao; Shi, Baozhong
Abstract : Glioma is one of the most common brain tumors and one of the most aggressive cancers. Although extensive progress has been made regarding to the diagnosis and treatment, the mortality in glioma patients is still high. Therefore, finding new therapeutic targets to the glioma is critical to the advancement in cancer treatment. Recently, the 37‐kDa laminin receptor precursor (37LRP) was reported to play important roles in occurrence of some types of cancer, indicating that this molecule may function as a key regulator in the tumor migration and metastasis. However, there is still no report to elucidate the correlation between 37LRP expression and glioma genesis and development. In this study, we found the higher expression of 37LRP in the glioma cells compared with the normal brain cells. We also indicated that the downregulation of 37LRP could affect the glioma biomarker expression and also weaken the proliferative, migratory, and metastatic capacity of glioma cells in vitro. Furthermore, 37LRP silencing inhibited the glioma tumor growth in vivo. Collectively, these data demonstrated that 37LRP regulates the metastasis of glioma cells in vitro and tumor growth in vivo, suggesting that 37LRP may function as a potential molecular target in the glioma treatment.